PENGARUH KUALITAS PELAYANAN, KUALITAS PRODUK, DAN KEPUASAN NASABAH TERHADAP LOYALITAS NASABAH PADA BANK CENTRAL ASIA KANTOR CABANG PEMBANTU DURI RIAU - Kurniawan, Teuku Reza (Sekolah Tinggi Ilmu Ekonomi Riau, 2018)
The purpose of this study is to determine how much influence the quality of service, product quality, and customer satisfaction of customer loyalty at central bank asia branch office Riau auxiliary thorn. Population in this research is all customer of central bank of asia of branch office of assistant of thorn which amounts 2889 people. Sampling is done by incindental sampling. Data analysis is done by using validity test, reliability, classical assumption, multiple linear regression, t-test, and F test. The test is conducted to know the influence of independent variable (independent variable) to the dependent variable. Based on the results of this study found that the quality of service, product quality and customer satisfaction have a positive and significant impact on customer loyalty at Bank Central Asia Duri Branch Office Riau